Response of SII cortex to ipsilateral, contralateral and bilateral flutter stimulation in the cat - Tommerdahl, Mark (BioMed Central, 2005)
BACKGROUND: A distinctive property of SII is that it is the first cortical stage of the somatosensory projection pathway that integrates information arising from both sides of the body. However, there is very little known about how inputs across the body mid-line are processed within SII. RESULTS: Optical intrinsic signal imaging was used to evaluate the response of primary somatosensory cortex (SI and SII in the same hemisphere) to 25 Hz sinusoidal vertical skin displacement stimulation ("skin flutter") applied contralaterally, ipsilaterally, and bilaterally to the central pads of the forepaws. A localized increase in absorbance in both SI and SII was evoked by both contralateral and bilateral flutter stimulation. Ipsilateral flutter stimulation evoked a localized increase in absorbance in SII, but not in SI. The SII region that responded with an increase in absorbance to ipsilateral stimulation was posterior to the region in which absorbance increased maximally in response to stimulation of the contralateral central pad. Additionally, in the posterior SII region that responded maximally to ipsilateral stimulation of the central pad, bilateral central pad stimulation approximated a linear summation of the SII responses to independent stimulation of the contralateral and ipsilateral central pads. Conversely, in anterior SII (the region that responded maximally to contralateral stimulation), bilateral stimulation was consistently less than the response evoked from the contralateral central pad. CONCLUSIONS: The results indicate that two regions located at neighboring, but distinctly different A-P levels of the anterior ectosylvian gyrus process input from opposite sides of the body midline in very different ways. The results suggest that the SII cortex, in the cat, can be subdivided into at least two functionally distinct regions and that these functionally distinct regions demonstrate a laterality preference within SII.